Genetic diversity and some biological characteristics of antibacterial yeasts isolated from natural honey and beeswax in Son La province - Pham, Anh Ngoc; Ha, Anh Kieu; Tran, Thuy Thi (Vietnam Journal of Science and Technology, 2023)
Yeast living in honey, an environment with high sugar content (up to 70 %, w/v), normally shows good resistance to the high level of osmotic pressure; they are of high potential for application in many fields. There were not many studies on the genetic diversity and biological characteristics of yeast from honey in Vietnam. This study aims to (1) evaluate the genetic diversity of antibacterial yeast isolated from natural honey and beeswax in Son La province by RAPD (Random Amplified Polymorphic DNA) and (2) study some biological characteristics of them. The research results may contribute to the scientific basis for screening yeast strains applied in different fields such as bioethanol and probiotic production. Sixty-eight yeast strains were isolated from natural honey and beeswax collected in Son La. Among them, twenty-one strains showed antibacterial activity against at least a tested bacterium including Escherichia coli, Bacillus subtilis, and Serratia marcescens. These yeast strains were genetically distinct in the RAPD analysis using M13 and (GTG)5 primers. Evaluation of yeast growing in the medium containing high glucose concentration (30 - 40 %, w/v) or high ethanol concentration (5 - 10 %, v/v) has shown some yeast strains that can tolerate high osmotic pressure and high ethanol concentration for different applications. YC.8 and YC.61 strains exhibited relatively good survival rates in two phases of digestion and have a wide pH range (2 - 7). YC.8 strain expressed the most potential for human or animal probiotics.